Human Resource Development Strategy in the Creative Industry of Sih Sasomo Art Studio - Carito, Danang Wikan; Cahyaningati, Retno; Hidayat, Zainul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This research aims to develop an effective human resource (HR) development strategy to enhance the competitiveness of the Sih Sasomo Art Studio in the creative industry. Focusing on HR needs, the study designs training programs in karawitan and puppetry, along with sustainability strategies to support local creative industry growth. Using a qualitative case study approach, data were gathered through in-depth interviews, participatory observations, and internal document analysis. The data analysis process involved data reduction, presentation, and conclusion drawing.The findings highlight three HR development priorities: strengthening skills in karawitan and puppetry, improving creative project management, and enhancing digital literacy. Community involvement in training activities significantly supports HR engagement and the sustainability of the studio. Theoretically, the research contributes to HR development literature in the creative sector by emphasizing the value of a community-based approach. Its originality lies in combining traditional arts with modern digital strategies. Practically, this study offers a strategic HR framework applicable to other art studios and similar organizations. However, the study is limited to the Sih Sasomo Art Studio context, and broader testing is needed to generalize the findings across different organizational settings.